Pre-disinfection columns to improve the performance of the direct electro-disinfection of highly faecal-polluted surface water. (15th September 2018) - Isidro, J.; Llanos, J.; Sáez, C.; Lobato, J.; Cañizares, P.; Rodrigo, M.A.
Abstract: This work presents the design and evaluation of a new concept of pre-disinfection treatment that is especially suited for highly polluted surface water and is based on the combination of coagulation-flocculation, lamellar sedimentation and filtration into a single-column unit, in which the interconnection between treatments is an important part of the overall process. The new system, the so-called PREDICO (PRE-DIsinfection Column) system, was built with low-cost consumables from hardware stores (in order to promote in-house construction of the system in poor countries) and was tested with a mixture of 20% raw wastewater and 80% surface water (in order to simulate an extremely bad situation). The results confirmed that the PREDICO system helps to avoid fouling in later electro-disinfection processes and attains a remarkable degree of disinfection (3–4 log units), which supplements the removal of pathogens attained by the electrolytic cell (more than 4 log units). The most important sizing parameters for the PREDICO system are the surface loading rate (SLR) and the hydraulic residence time (HRT); SLR values under 20 cm min −1 and HRT values over 13.6 min in the PREDICO system are suitable to warrant efficient performance of the system. Highlights: Pre-treatment helps to prevent fouling in later electro-disinfection processes. Excellent disinfection of highly polluted water (3–4 log units). The pre-treatment steps can be combined into a single-column unit with an in-house design. The pre-disinfection column can be easily integrated with electro-disinfection.